0

# What is the product of 7-3x?

Updated: 4/28/2022

Wiki User

9y ago

10

Jennings Hettinger

Lvl 10
3y ago

Wiki User

9y ago

7 times -3x = -21x

Earn +20 pts
Q: What is the product of 7-3x?
Submit
Still have questions?
Related questions

75

### What is the answer to 2x 5-73x-2?

156 i think, but im not sure.

### What is 3x - 4 equals 7?

3x - 4 = 73x = 11x = 3.66666...

### How do you factor 26x to the fourth - 73x squared y plus 20y squared?

(13x^2 - 4y)(2x^2 - 5y)

### What is the value of a 20 gauge Belgian Browning shotgun serial no 73x 49694?

You need to include a model number with this question to get the correct fiqures.

### What is 5X-78X equals 68?

Grouping like terms, -73x = 68 Therefore, 68/-73 = x x = -0.93150684 recurring (that is, -0.9315068493150684...)

### Solve for the value of x in the expression -6x-73x plus 12?

An expression cannot be solved: only an equation or inequality has solutions.

1973

### How do you rewrite this equation so that y is a function of x -- 3x plus 5y equals 7?

Because of the limitations of the question software, it was not possible to determine what the original equation was supposed to be, so we assumed it is 3x + 5y = 7. It could have just as easily been 3x - 5y = 7, or even 3x/5y = 7.So, let's solve them all for x.3x + 5y = 73x = 7 - 5yx = (7 - 5y)/3How about 3x - 5y = 7?3x - 5y = 73x = 7 + 5yx = (7 + 5y)/3And 3x/5y = 7?3x/5y = 73x = 35yx = 35y/3 Solving for y The above equations wrote the equation so that x is a function of y, not the other way around. Here's how to rewrite the equation so that y is a function of x: 3x + 5y = 7 5y = -3x + 7 y = (-3x + 7)/5

### Three times the sum of a number and -7 is 12?

In algebra, this would be how you figure out this equation:3x-7=12+7 +73x=19/3 /3x=19/3x= 6 1/3Therefore, the value of your variable ("x") is 6 and one third.

### What is the largest whole number in the solution set for 6x plus 7 less than 3x plus 10?

6x + 7 < 3x + 106x - 3x

### How do you solve 3X plus 7 equals 4X?

3x+7=4x-73x=(-)7+4x-4x(-)1x=(-)7________(-)1x=7add (-3x) to each side of equation3x +7 = 4x-3x +3x +7 = 4x -3x0 +7= 1x7=x